The Role of Artificial Intelligence in Designing More Modern Furniture Towards the Bauhaus Movement (Journal of Architectural Design, 2023)
With the development of the economy and the tools of scientific and technological intelligence, Artificial Intelligence (AI) has emerged and entered the field of interior design of modern homes, including the design of home furniture. AI in the field of home furniture design provided many features which significantly helped in reducing the daily operating time and energy cost, as well as improving the quality of products. Hence this study aims to explore the role of Artificial Intelligence (AI) and its applications in achieving more modern and innovative furniture towards the Bauhaus. The study showed that AI plays a crucial role in transforming the furniture design industry in a more modern way, since AI applications introduced new horizons for designers and manufacturers to develop designs that are innovative, sustainable, and of high quality. Therefore, AI applications help in improving the design process, choosing optimal materials, and enhancing the comfort and sustainability of furniture, due to its ability to analyze big data and use advanced algorithms, providing designers with valuable information and directing them towards making better decisions. Consequently, the integration of human creativity with the power of calculation and analysis of AI opens wide horizons to design more modern, unique, and sustainable furniture